Changes in injury risk mechanisms after soccer-specific fatigue in male youth soccer players - Lehnert, M.; De Ste Croix, M.; Xaverova, Z.; Botek, M.; Varekova, R.; Zaatar, A.; Lastovicka, O.; Stastny, P. (Journal of Human Kinetics, 2018)
The aim of this study was to examine the acute effects of soccer specific fatigue on muscular and neuromuscular function in male youth soccer players. Elite soccer players (n = 20; age 15.7 ± 0.5 y; body height 177.75 ± 6.61 cm; body mass 67.28 ± 8.29 kg) were measured before and after soccer specific exercise (SAFT). The reactive strength index (RSI) was determined by a drop jump test, leg stiffness (LS) by a 20 sub-maximal two-legged hopping test, and a functional hamstring to quadriceps strength ratio from isokinetic concentric and eccentric strength of the dominant and non-dominant leg (measured at angular velocities of 1.05 rad · s-1 and 3.14 rad · s-1). Metabolic response to the SAFT was determined by blood lactate and perceived exertion was assessed by the Borg scale. After simulated match play, a significant decrease in absolute LS (t = 4.411; p < 0.001; 2 = 0.48) and relative LS (t = 4.326; p < 0.001; 2 = 0.49) was observed and the RSI increased significantly (t = 3.806; p = 0.001; 2 = 0.40). A reduction in LS found after the SAFT indicates possible reduction in dynamic knee stabilization. However, if we consider the changes in other observed variables, the present study did not clearly confirm that fatigue induced by a soccer specific protocol increased the risk of ACL and hamstring injury. This may be attributed to the simulated rather than actual match play used in the present study.